Pulmonary hypertension in mitral stenosis patients submitted to percutaneous balloon mitral valvuloplasty: an innocent bystander?. (4th February 2022) - Ferreira, V; Rodrigues, I; Almeida Morais, L; Bernardes, L; Cacela, D; Patricio, L; Galrinho, A; Reis, JP; Grazina, A; Castelo, A; Cruz Ferreira, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Percutaneous balloon mitral valvuloplasty (PBMV) is the cornerstone of the treatment of rheumatic mitral stenosis (MS) in suitable patients. Pulmonary hypertension (PH) is a common coexisting finding and an indication for intervention. We sought to assess the influence of PH in PBMV immediate results and in very longterm outcome. Methods: Between 1991 and June 2021, 202 consecutive patients underwent PBMV in a single tertiary centre. Clinical data, echocardiographic parameters, and MACE (cardiovascular mortality, need for percutaneous or surgical mitral reintervention) were analysed. Results: Mean age was 47.3 ± 13.6 years and 89.6% were women. A previous commissurotomy or PBMV was found in 10.4% and mean Wilkins score was 7.6 ± 1.4. PH, defined as pulmonary artery systolic pressure (PASP) ≥45mmHg, was present in 32.7% of patients. A successful procedure was achieved in 89.1% of total population. Mean mitral valve (MV) gradient decreased from 13.1 to 5.0 mmHg (p < 0.001) and MV area increased from 1.1 to 1.8 cm2 (p < 0.001). A significant reduction also occurred in left atrium diameter (48.8 to 46.8 mm, p < 0.001) and PASP (50.5 to 38.5 mmHg, p < 0.001). During a mean follow-up of 12.0 ± 8.8 years, 7 cardiovascular deaths occurred (3.5%) and 33.2% of patients needed MV reintervention. Baseline PH did not impact immediate success and was not related with MACE in the follow-up. However, PH persistence after PBMV was correlated with unsuccessful procedure (p = 0.023) and with the occurrence of MACE during FU (HR 3.3, CI 95% 1.1-9.6, p = 0.028 and Kaplan-Meier analysis, log-rank 0.020). Conclusions: PBMV in patients with MS and PH is a safe and effective intervention, achieving a significant decrease in PASP after procedure. Baseline PH was not associated with success or MACE. However, PH persistence after PBMV, correlated with worse prognosis in longterm follow up. Special attention and further investigation for this subgroup is needed.